When the past becomes the future: The problem of policies in 'left behind' places - Tobias Johannes Hertrich; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2024)
The concept of “left behind” places encompasses economic, demographic, infrastructural, social and political aspects. Different studies of the left behind place concept focus on different aspects or combinations of these. Hertrich and Brenner (2024) assume an interplay of many aspects that lead to the left behind feeling but emphasize the emerging dynamics of opinion. The purpose of this paper is to analyze this interaction of individual factors in detail in a case study and thus gain a deeper understanding of the processes that presumably play a role in many other regions. Contrary to perception, the labor market region (LMR) Gera is developing dynamically in many parameters. We find that although the reasons for the left behind feeling can be assigned to the pillars of the model, in most cases they relate to the past. We conclude that the political measures and developments in the LMR to date have not had an effect due to the strong formation of opinion based on historical events. In addition, the dynamics of opinion formation play a major role in left behind places, which has so far been neglected in politics. – – Das Konzept der zurückgelassenen" Orte umfasst wirtschaftliche, demografische, infrastrukturelle, soziale und politische Aspekte. Verschiedene Studien zum Konzept der zurückgelassenen Orte konzentrieren sich auf unterschiedliche Aspekte oder Kombinationen dieser Aspekte. Hertrich und Brenner (2024) gehen von einem Zusammenspiel vieler Aspekte aus, die zum "Left behind"-Gefühl führen. Das Ziel dieser Arbeit ist es, dieses Zusammenspiel einzelner Faktoren in einer Fallstudie detailliert zu analysieren und so ein tieferes Verständnis für die Prozesse zu gewinnen, die vermutlich in vielen anderen Regionen eine Rolle spielen. Entgegen der Wahrnehmung entwickelt sich die Arbeitsmarktregion (AMR) Gera in vielen Parametern dynamisch. Wir stellen fest, dass zwar die Gründe den Säulen des Modells zugeordnet werden können, sich aber in den meisten Fällen auf die Vergangenheit beziehen. Wir schließen daraus, dass die politischen Maßnahmen und Entwicklungen in der AMR aufgrund der starken Meinungsbildung aufgrund historischer Ereignisse kaum Wirkung entfalten. Die Dynamik der Meinungsbildung spielt eine große Rolle, die in der Politik bisher vernachlässigt wurde.
Keywords: O18; O20; R11; R12; 330; left behind place; feeling left behind; case study; lagging region; policy measures; regional development; territorial inequality